PENGARUH PENDAMPINGAN BELAJAR ORANG TUA PADA MASA PANDEMI COVID-19 TERHADAP PRESTASI BELAJAR SISWA KELAS V DI SDN DURI KEPA 05 - Heni Oktavia; Abdul Halim (Jurnal Inovasi Penelitian, 2021)
This research is motivated by the phenomenon of the lack of parental assistance during learning from home so that student learning achievement is less than optimal. Parental learning assistance that is carried out consistently will be able to affect student learning achievement. The purpose of this study was to determine whether there is an effect of parental learning assistance on the learning achievement of fifth grade students at SDN Duri Kepa 05. This research is a quantitative study using a survey method. The population in this study were students of class V C, totaling 30 students. This research was carried out for nine months starting from February to October 2021. The data collection technique in this study used a questionnaire distributed through an online google form. The results of the hypothesis by using the partial test (t test) obtained = 8.158 > = 2.048 with a significance of 0.000 <0.005. This result shows that it is rejected and accepted, which means that there is a positive and significant influence between Learning Assistance and Learning Achievement.